2021
DOI: 10.3389/fonc.2021.654684
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CD276 in Cancers

Abstract: ObjectiveAberrant expression of the immune checkpoint molecule, CD276, also known as B7-H3, is associated with tumorigenesis. In this review, we aim to comprehensively describe the role of CD276 in malignancies and its potential therapeutic effect.Data SourcesDatabase including PubMed, EMbase, Cochrane Library, CNKI, and Clinical Trails.gov were searched for eligible studies and reviews. Study selection: Original studies and review articles on the topic of CD276 in tumors were retrieved.ResultsCD276 is an immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 86 publications
1
56
0
Order By: Relevance
“…Previous studies have consistently reported CENP-U to be positively correlated with HMGB2 in OV (24), and it has been shown that knockdown of CENP-U expression in bladder cancer can decrease the expression of HMGB1 (22). Among other immune checkpoints, (I) the PD-1 and PD-L1 axis was shown to act as a mechanism of tumor cell escape from host immunity (38), (II) LAG3 was reported to exert a suppressive effect on activated T cells (39), (III) VEGFA was found to inhibit the trafficking of cytotoxic T lymphocyte (CTL) and the maturation of DCs ( 40), (IV) CD276 was recently identified as a T cell inhibitor (41), and (V) CXCL9 and CXCL10 were demonstrated to promote the differentiation of naïve T cells to T helper (Th) cells (42); however, (VI) the effect of other immune checkpoints remains relatively controversial. From the abovementioned results, we can surmise that, compared with immune stimulators correlated to CENP-U expression, the immune inhibitors with correlations had a more profound effect on tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently reported CENP-U to be positively correlated with HMGB2 in OV (24), and it has been shown that knockdown of CENP-U expression in bladder cancer can decrease the expression of HMGB1 (22). Among other immune checkpoints, (I) the PD-1 and PD-L1 axis was shown to act as a mechanism of tumor cell escape from host immunity (38), (II) LAG3 was reported to exert a suppressive effect on activated T cells (39), (III) VEGFA was found to inhibit the trafficking of cytotoxic T lymphocyte (CTL) and the maturation of DCs ( 40), (IV) CD276 was recently identified as a T cell inhibitor (41), and (V) CXCL9 and CXCL10 were demonstrated to promote the differentiation of naïve T cells to T helper (Th) cells (42); however, (VI) the effect of other immune checkpoints remains relatively controversial. From the abovementioned results, we can surmise that, compared with immune stimulators correlated to CENP-U expression, the immune inhibitors with correlations had a more profound effect on tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the expression of CTHRC1 was positively correlated with ICP gene CD276, which was identified a promising therapeutic target for malignant tumors (Additional file 10 : Fig. S10d) [ 64 ]. These results may indicate the underlying mechanisms for CTHRC1 regulation of immune cell function in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, CD276 is also abnormally expressed in a variety of tumors and participates in tumor proliferation, apoptosis, differentiation, invasion and interepithelial transformation. Usually CD276 is up-regulated in tumors and is associated with poor prognosis of patients ( Liu S. et al, 2021 ). In NSCLC, a previous meta-analysis found that the high expression of CD276 was significantly associated with patients’ lymph node metastasis and advanced TNM staging ( Wu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%